The Relationship between E-Service Quality on Satisfaction And Trust, and its Implications Related to Word of Mouth and Loyalty of E-Commerce Consumers in Indonesia - Wulandari, Astri; Marcelino, Dandy; Aprilina, Riska (Journal of Ecohumanism, 2025)
Electronic Commerce (E-Commerce) is a strategy that can be implemented to achieve business targets and goals. The increasingly developing digital era means that various aspects also have the potential to utilize technology in various lines. The various platforms, applications and digital features used can add value to company performance, because these platforms can help optimize business performance and strategy. The use of digital technology applies not only to manufacturing companies but also to service companies. Service is an important indicator of consumer satisfaction. Good service, quick response, willingness to accept feedback and criticism are advantages for the company. Because if consumers are satisfied with the services provided, it will also have a positive influence on the company. Apart from increasing satisfaction, good service will also increase consumer trust in the company. Associated with the digital era, service quality includes the e-service quality category. Nowadays, many services using digital media have been implemented considering the convenience and time efficiency. Quality service will also influence word of mouth and consumer loyalty. If consumers are satisfied with the service they receive, they will tell family and friends about this, which will indirectly increase promotion and branding. Then, satisfied consumers will also increase loyalty by making repeat purchases, thereby increasing engagement and company performance. Based on the results of data processing using the SEM method and the TAM model, a positive influence between variables was obtained.